Orthokeratology and Contact Lens Quality of Life Questionnaire (OCL-QoL). Issue 5 (September 2018) - McAlinden, Colm; Lipson, Michael
Abstract : Objectives: To develop a quality of life (QoL) instrument for patients fitted with Orthokeratology (OrthoK) and other modalities of contact lenses. Methods: A 45-item pilot questionnaire was developed from an extensive literature review, focus groups, and interviews. Subsequently, 234 participants fitted with contact lenses (OrthoK, soft lenses, and gas permeable lenses) or spectacles completed the pilot questionnaire. Rasch analysis was used to assess the psychometric properties in terms of person separation, item fit statistics, category threshold ordering, differential item functioning (DIF), and targeting. A subset of participants completed the final questionnaire twice (1 week apart) and the repeatability assessed (within-subject standard deviation). The Spearman rank–order correlation coefficient between the questionnaire score and binocular visual acuity was calculated to assess construct validity. Results: Inspection of category probability curves suggested that one category was underused and the response options were collapsed. Furthermore, Rasch analyses indicated 22 items misfitted the model and were removed. The final questionnaire contained 23 items with a person separation of 2.18, item fit statistics within the range 0.83 to 1.15, targeting 1.05 logits, and no significant DIF (<0.8 logits). The repeatability ( S r ) was 4.21 and there was no correlation between questionnaire scores and binocular visual acuity ( r s =0.03, P =0.65). Conclusions: The Orthokeratology and Contact Lens Quality of Life Questionnaire demonstrated excellent psychometric properties and is capable of measuring vision-related QoL in patients fitted with various forms of contact lenses including OrthoK lenses. The tool is scored on a 0 to 100 interval level scale with higher scores indicating better QoL.